Jeopardizing Democracy by Shrinking Participation? Two Years of Giorgia Meloni’s Government - Domenico Andrea Schiuma (Nuovi autoritarismi e democrazie: diritto, istituzioni, società)
The Government led by Giorgia Meloni has now ruled Italy for two years. When she became Prime Minister, some commentators were worried about her fascist heritage. While so far, she has not resurrected fascism, if one believes participation and public discussion are the core to democracy, then the actions of the Meloni Government should be monitored closely. In particular, this concerns three reforms, here described, which shrink citizens’ role in democracy and, in this way, possibly start jeopardizing it